ANALISIS FASILITAS DI TERMINAL LEUWI PANJANG, KOTA BANDUNG - Siddiq, Raden Herdian Bayu Ash (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
Leuwi Panjang Terminal is one of the Type A passenger terminals in the city of Bandung. As a type A terminal that functions to serve public passenger vehicles for inter-city inter-provincial transportation (AKAP), and cross-border transportation between countries, inter-city transportation within the province (AKDP), city transportation (AK) and rural transportation (ADES), the terminal Leuwi Panjang must meet service standards for public passenger transportation. The research aims to measure the completeness of existing service facilities at the Leuwi Panjang terminal based on the Minister of Transportation Regulation No. 40 of 2015 concerning Service Standards for the Implementation of Public Transport Passenger Terminals. This research was conducted by conducting direct observation and taking documentation at the research location. After the data is collected then data analysis is carried out. From the results of data analysis, it was concluded how the service conditions at the Leuwi Panjang Terminal were. From the results of the study, it was found that the service facilities at the Leuwi Panjang terminal were quite dominant with a percentage of 61% of the total 41 service items that must be owned by a type A terminal, 39% of incomplete facilities at the Leuwi Panjang terminal were in the Safety and Convenience aspect. In connection with the results of the research, it is necessary to make adjustments in the form of rehabilitation and renovation at the Leuwi Panjang Terminal to improve service standards.